Impact of urban heat islands on human health in India – a systematic review protocol - Varughese, Chinnu S.; Mani, Sapna M.; Vincent, Vineetha; Cherian, Sunu A.; Kurian, Nisha (International Journal Of Community Medicine And Public Health, 2025)
Background: Worldwide, urbanization is occurring at an accelerated rate, especially in India. The development of urban areas contributes to urban heat island (UHI) phenomenon. Though the health effects of UHIs have been studied in various urban areas across the world, there is a need to develop evidence in India. This is essential for implementing effective and country-specific interventions aimed at mitigating the UHI effect while expanding urban areas in the country. The objective of this review is to describe the human health impacts of urban heat islands in India. The review will consider studies that focus on urban populations irrespective of age and sex, which report on health effects due to urban heat islands, or changes in ambient temperatures due to urbanization. Methods: This review will search for both published and unpublished studies. The information sources to be searched will include Medline (PubMed), Embase, Epistemonikos, Virtual Health Library, PsychINFO (EBSCO), Mednar, Dissertation Abstracts International, Proquest dissertations and theses, World Health Organization (WHO) website and Google Scholar. Studies published from database inception till current date, as well as those published in English, will be included. Two independent reviewers will conduct a critical appraisal of eligible studies, assess the methodological quality, and extract the data. Conclusions: This review will add to the body of evidence on urban heat island effects on human health and help to inform urban policy and planning. Trial registration number: PROSPERO - CRD42024588528